Perceived Organizational Support dan Task Performance : Peran Mediasi Work Engagement - Yulia, Lika; Sanusi, Fauji (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2021)
The purpose of this study was to examine the relationship between Perceived organizational support and task performance and the mediating effect of work engagement variables on the relationship between Perceived organizational support and task performance. Data analysis using PLS version 3.29, data collection using a questionnaire distributed to employees of PT. Latinusa Cilegon, Banten and in-depth interviews. The results showed that perceived organizational support positively and significantly affected task performance and work engagement. It can be added that work engagement is able to mediate the relationship between Perceived organizational support and task performance